Understanding the Relationship Between Complicated Grief Symptoms and Patterns of Personality Disorders in a Substance Users’ Sample: A Network Analysis Approach - Masferrer, Laura; Mancini, Anthony D.; Caparrós, Beatriz (Frontiers in Psychology, 2020)
Background. The presence of personality disorders is greatly prevalent among substance users. Personality disorders could increase vulnerability to complicated grief symptoms. Bereavement is commonly overlooked among substance users. We used network analysis to estimate the structure of relations between patterns of personality disorders and complicated grief symptoms among a bereaved substance using population. Methods. Complicated grief and personality disorders were assessed in a sample of 196 bereaved substance users. We use the graphical LASSO to compute a regularized partial correlation network revealing associations among different patterns of personality disorders and complicated grief symptoms. Results. In a network involving nodes for personality disorders and symptomatology of complicated grief, patterns of depressive and paranoid personality disorder showed small relationships to complicated grief symptoms. All other personality disorders showed negligible to no relationship to complicated grief symptoms. Further, in the overall network, complicated grief showed the lowest level of centrality, suggesting it is independent of personality disorder, whereas depressive and paranoid personality disorder symptoms showed the highest centrality. Conclusions. Network analysis can be used to understand the relationships among higher-level constructs such as disorders. We found that complicated grief is largely independent of patterns of personality disorders with the exception of depressive and paranoid. Findings have implications for assessment and appropriate treatment of complicated grief symptoms and substance use disorder.